Reconfiguring ferromagnetic microrod chains by alternating two orthogonal magnetic fields. (11th July 2018) - Cheng, Rui; Zhu, Lu; Huang, Weijie; Mao, Leidong; Zhao, Yiping
Abstract: It is well-known that ferromagnetic microrods form linear chains under an external uniform magnetic field B and the chain length is strongly dependent on the applied field, the applied time duration, and the microrod density. When the chains become long enough and the B -field switches to its orthogonal direction, an irreversible morphological transition, i.e. a parallel linear chain array to a 2D network, is observed. The formation of the network depends on the ratio of the average chain length L and separation D, L / D, as well as the magnitude of the changed B -field. When the chain pattern has an L / D larger than a critical value, the network structure will be formed. Such a critical L / D ratio is a monotonic function of B, which determines the bending length of each magnetic chain during the change of B -fields. This morphological change triggered by external magnetic field can be used as scaffolds or building blocks for biological applications or design smart materials.